Trombinol, a bioactive fraction of Psidium guajava, stimulates thrombopoietin expression in HepG2 cells - Guntur Berlian (Asian Pacific Journal of Tropical Biomedicine, 2017)
Objective: To study the regulation of trombinol on thrombopoietin, an essential regulator of thrombocyte production. Methods: Effect of trombinol on thrombopoietin regulation was evaluated at the mRNA and protein levels in human hepatoma HepG2 cells. The mRNA expressions were revealed by PCR and real-time PCR, while the protein expressions were analyzed using western blotting and human ELISA kit. Statistical differences between the test were determined by student's t-test with P < 0.05 was considered statistically significant. Results: Trombinol significantly increased the expression of thrombopoietin at the level of mRNA and protein secretion in HepG2 cell lines. Trombinol with the concentration of 15 μg/mL, positively induces 2.5-fold of thrombopoietin expression. Up-regulation of GABP, a transcription factor of thrombopoietin, is suggested to be involved in cellular regulatory mechanisms of trombinol. Here, our result shows convincing evidence that trombinol affects the thrombopoietin productions in vitro. This molecular explanation of thrombopoietin's stimulating function is in line with the traditional use of Psidium guajava for treatment of diseases involving thrombocytopenia. Conclusions: Thrombopoietin stimulating function of trombinol could be potentially considered as one of alternative treatment for thrombocytopenia-related cases, including post chemotherapy shock, dengue fever and liver failure.